Hypereosinophilic Syndrome, Cardiomyopathies, and Sudden Cardiac Death in Superinvasive Opisthorchiasis. (9th May 2019) - Bychkov, Vitaly G.; Zolotukhin, Vladimir M.; Khadieva, Elena D.; Kulikova, Svetlana V.; Petrov, Ivan M.; Berdinskih, Svetlana G.; Lazarev, Semen D.; Morozova, Lola F.; Morozov, Evgeny N.
Abstract : Cardiovascular pathology in patients with superinvasive opisthorchiasis is characterized by severe changes in haemodynamics and myocardial metabolism, impaired automatism, excitability, and conduction of the heart muscle. An analysis of 578 cases (medical and outpatient records and reports of pathoanatomical and forensic autopsies) recorded in healthcare facilities treating opisthorchiasis patients with a hyperendemic focus was carried out. We identified a set of cardiac changes in patients with hypereosinophilic syndrome associated with superinvasive opisthorchiasis infection, classified the pathological processes in accordance with ICD-10, and described their pathogenesis.